Advanced Burkitt Lymphoma in Sub-Saharan Africa Pediatric Units: Results of the Third Prospective Multicenter Study of the Groupe Franco-Africain d’Oncologie Pédiatrique - Gabrielle C. Bouda; Fousseyni Traoré; Line Couitchere; Marie-Anne Raquin; Koffi M. Guedenon; Angele Pondy; Claude Moreira; Mbola Rakotomahefa; Mhamed Harif; Catherine Patte (Journal of Global Oncology, 2019)
PURPOSE: To evaluate the results of an intensive polychemotherapy regimen for Burkitt lymphoma (BL) in sub-Saharan African pediatric centers. PATIENTS AND METHODS: Children with advanced-stage BL (stages II bulky, III, and IV) treated with the GFAOP–Lymphomes Malins B (GFALMB) 2009 protocol in 7 centers between April 2009 and September 2015 were prospectively registered. Treatment regimen contained a prephase with cyclophosphamide followed by 2 induction courses (cyclophosphamide, vincristine, prednisone, high-dose methotrexate [HDMTX]), 2 consolidation courses (cytarabine, HDMTX), and a maintenance phase only for stage IV. HDMTX was given at the dose of 3 g/m2. RESULTS: Four hundred patients were analyzed: 7% had stage II bulky, 76% stage III, and 17% stage IV disease. Median age was 7.3 years, and sex ratio was 1.9:1 (male:female). A total of 221 patients received the whole protocol treatment and 195 achieved complete remission (CR), 11 of them after a second-line treatment. Treatment abandonment rate was 22%. One hundred twenty-five patients died, of whom 49 deaths were related to treatment toxicity. A total of 275 patients are alive, including 25 despite treatment abandonment, but only 110 are known to be in CR with a follow-up > 1 year, indicating a high rate of loss to follow-up. Twelve-month overall survival (OS) was 60% (95% CI, 54% to 66%) and 63%, 60%, and 31%, respectively, for stage II bulky, III, and IV. Patients with stage III disease who started second induction course within 34 days had OS of 76%, versus 57% (P = .0062) beyond 34 days. CONCLUSION: The GFA-LMB2009 protocol improved patients’ survival. Early dose intensity of treatment is a strong prognostic factor. Improving supportive care and decreasing loss to follow-up are crucial.